PENDAMPINGAN BELAJAR DENGAN PERMAINAN EDUKATIF ULAR TANGGA UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA SMP NEGERI 2 TEHORU - Nana Ronawan Rambe; Fenny Adnina Daulay (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2023)
Teaching and learning is an integral process of providing education. In carrying out learning activities it is expected that students can play an active role during the implementation of activities taking place. However, the fact that passive students participate in teaching and learning activities has a direct impact on student learning outcomes. monotonous teaching. Therefore this community service activity aims to increase student learning activeness in learning. The method used is the PAIKEM method (active, innovative, creative, effective and fun learning). The results of the community service activities carried out at SMP Negeri 2 Tehoru in class VIII showed significant results, namely that 27 students had scores above the KKM (70.0) while 3 students had scores below the KKM. So it can be concluded that community service activities carried out in class VIII SMP Negeri 2 Tehoru by conducting learning using the snakes and ladders learning model are said to be able to increase the effectiveness of student learning.